The State of the Welfare State: Advice, Governance and Care in Settings of Austerity. Issue 1 (1st January 2022) - Koch, Insa; James, Deborah
ABSTRACT: Contemporary attempts to govern 'the state of the welfare state' are as much about moral endeavours as they are about political and economic imperatives. Such is the argument put forward in this Introduction, which focuses on the work that advisers perform in settings of austerity across Europe. Advisers are often the last call for help for their clients/dependents who find themselves increasingly at the mercy of local authorities, immigration regimes, landlords, banks and debt collection agencies. But competing visions of moral worth and social justice continue to permeate the everyday deliberations of those who administer, support and advocate advice. Struggles and dilemmas over how best to provide assistance and balance individuals' moral judgments against the collective good frequently occur. We explore both the dovetailing of and divergence between domains and roles, in disrupting as well as reproducing dominant logics of extraction and accumulation.